STUDY OF EXCELLENT RECEPTIONIST SERVICE IN RECEIVING GUESTS AT THE MARKETING OFFICE OF PARADISE RESORT, CIPUTAT, SOUTH TANGERANG - Riri Oktarini (International Journal Management and Economic, 2023)
The purpose of this research is to find out the excellent service provided by the receptionist to guests or customers of the Marketing Office Paradise Resort Ciputat South Tangerang and to find out what problems the receptionist experiences when receiving guests or customers at the Marketing Office Paradise Resort Ciputat South Tangerang. Based on the data obtained, excellent service is essential in running a business, especially a goods or services business. One of the ways the Paradise Resort Marketing Office receptionist provides excellent service to guests is that they must be ready and responsive in any case to provide services for guest satisfaction. For example, they were helping to patiently provide more precise and detailed information regarding the products offered to guests. This can provide comfort to guests and additional value for the company in its services so that guests will feel comfortable with the services provided. Meanwhile, the problem the receptionist faces in receiving guests at the Marketing Office of Paradise Resort Ciputat, South Tangerang, is the lack of experience or flying hours obtained by the receptionist because the receptionist is still a fresh graduate, so she is still unable to handle the work that must be done if there are more than 2 ( two) work at the same time. The author suggests that companies carry out additional training or training regularly to increase receptionists' skills or abilities at work. This is very beneficial if the receptionist is equipped with additional skills. Their performance can be even better.